Harnessing trade for structural transformation in sub-Saharan Africa: monitoring exports, South-South trade and commodity price volatility - Hagan, Maame Ayegua, author; Braunstein, Elissa, advisor; Vasudevan, Ramaa, committee member; Numa, Guy, committee member; Costanigro, Marco, committee member (Colorado State University. Libraries, 2021)
This dissertation consists of three main empirical papers that lie at the intersection of international trade and (under) development. In particular, motivated by the proposition that structural change in sub-Saharan Africa (SSA) is needed for sustained growth, the papers build on each other to highlight different dimensions in SSA's quest for structural transformation within the context of global integration. Together, the papers explore the linkages between structural transformation and exports, South-South trade and commodity price volatility. Much of the literature on pathways for SSA to catch-up is centered on the success in East Asia's export-oriented industrialization and the replicability of this model. While there have been calls to apply the exact export-oriented industrialization recipe that transformed several economies in East Asia, evidence from SSA about the impact of this approach is not well-documented quantitatively. The first empirical paper (chapter 3) attempts to address this gap in the existing literature. Developing countries, especially those in SSA, have been involved in the production of primary commodities which were traded for imports of technologically-intensive manufacturing commodities, primarily from rich countries in the global North. However, the 2008 global economic crisis, which began in the global North but circulated to the South particularly through its impact on global trade, raised concerns about the desirability of export systems that depended on Northern demand. This experience encouraged developing countries to deepen their efforts to diversify their trade beyond North-South. Thus, South-South trade became one main alternative for accelerating structural transformation and achieving sustainable development. The second empirical paper (chapter 4) explores the prospects and implications of South-South trade as opposed to North-South trade as drivers of structural transformation in SSA. The relationship between terms of trade fluctuations and macroeconomic performance has been a deeply debated topic in the growth and development literature. The end of the recent "commodity super cycle" has renewed the discussion of the impact of large terms of trade shocks and the resulting ways of adjustment that follow. Many existing studies use the aggregate terms of trade as a proxy for commodity terms of trade while others have used different variations of the commodity terms of trade that rely on the price of only a few commodities. To address this, the final chapter (chapter 5) uses a newly developed, comprehensive, country-specific commodity terms of trade index and a broad sample of countries (with a special eye for SSA) to study the impact of persistent commodity price volatility on key variables that influence structural transformation in an economy. To put the results from the papers into perspective, where necessary, we compare the potential differences and similarities that exist with emerging and developing economies in America and Asia.
Keywords: international trade; growth; exports; SSA; commodity price volatility